Solve for p -6p-21=3p-12

Math
-6p-21=3p-12
Move all terms containing p to the left side of the equation.
Tap for more steps…
Subtract 3p from both sides of the equation.
-6p-21-3p=-12
Subtract 3p from -6p.
-9p-21=-12
-9p-21=-12
Move all terms not containing p to the right side of the equation.
Tap for more steps…
Add 21 to both sides of the equation.
-9p=-12+21
Add -12 and 21.
-9p=9
-9p=9
Divide each term by -9 and simplify.
Tap for more steps…
Divide each term in -9p=9 by -9.
-9p-9=9-9
Cancel the common factor of -9.
Tap for more steps…
Cancel the common factor.
-9p-9=9-9
Divide p by 1.
p=9-9
p=9-9
Divide 9 by -9.
p=-1
p=-1
Solve for p -6p-21=3p-12

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top